WEB-BASED VIDEO EDITOR - Myrzakhan, Rakhat; Toganbay, Nurtau; Abdirakhym, Ayazhan (Nazarbayev University School of Engineering and Digital Sciences, 2024)
This thesis describes the development of a web-based video editor that functions entirely on the client side, thus avoiding any server-side processing. The main goal of this project is to deal with frequently occurring problems in current web-based video editors: resource-intensiveness, slow experience, and privacy risks from server-run video processing. Featuring improved performance, bandwidth saving, and security/privacy by utilizing the WebCodecs and Service Worker APIs provided by modern web browsers with several optimizations. The video editor can do real-time manipulation of frames on a video, changing opacity, color, saturation, brightness, and adding blur effects. Users can upload multiple videos for editing, perform trimming and track removal operations, and export videos in multiple ratios and resolutions. With the easy-to-use and intuitive interface, users can navigate and control their way through to a hassle-free editing experience. This thesis describes building and developing the functions of the video editor and analyses problems encountered and ideas used to solve them. Performance evaluations show huge improvements in export times and reduced file sizes compared to current server-side and client-side video editors. The project ends by listing possible extensions such as support for audio manipulation, animations, auto-captioning with AI, and more advanced text overlay functionalities. With this work, we seek to make a high-speed, safe, and user-friendly application that can be integrated with similar applications in web video editing.
Keywords: Type of access: Open Access